PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) MENURUT PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 6 TAHUN 2018 (CONTOH KASUS: DESA LEMBANGSARI KECAMATAN RAJEG KABUPATEN TANGERANG) - Wiranti Agustina Ningrum; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
Land has a high economic value and can be the obligation of every individual to maintain and maintain its existence as an object that is considered very economical on the grounds that land has benefits for the implementation of development, not least land can cause various kinds of problems for humans so that its use must be controlled. as well as possible so that new problems do not arise in people's lives. The provisions in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states "Earth and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people". Complete Systematic Land Registration, which is abbreviated as PTSL, is a land registration activity for the first time that is carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in one village/kelurahan area or another name of the same level, which includes the collection of juridical data regarding one or more Some land registration objects for registration purposes, this is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018. The free land certificate program provided by the government is a concept from President Jokowi, with the aim of reducing land problems in the midst of society. This program has been implemented and is being carried out in stages. In the context of realizing the presence of the state in the land sector by providing legal certainty of land rights as proof of ownership rights as mandated in Article 19 of the UUPA, the government is obliged to carry out land registration throughout the territory of the Republic of Indonesia.